Phenotypic Plasticity Conferred by the Metastatic Microenvironment of the Brain Strengthens the Intracranial Tumorigenicity of Lung Tumor Cells - Wei, Xu-Ge; Bi, Ke-Wei; Li, Bo (Frontiers in Oncology, 2021)
Lung cancer is the leading cause of cancer-related deaths and is the primary source of brain metastases. Despite great advances in the study of the genetics and etiology of lung cancer in previous decades, the identification of the factors and mechanisms underlying the brain metastasis of lung tumors is still an open question. In this study, the results of bioinformatic conjoint analysis revealed that the metastatic microenvironment in the brain conferred lung tumor cell phenotypic plasticity, characterized by neural cell-like and embryonic–stem cell-like features. Meanwhile, the metabolic phenotype of the educated tumor cells underwent transition characterized by oxygen-related metabolism. The results of the experiments demonstrated that the downregulation of HOXB9 weakened the tumorigenicity of lung tumor cells. Bioinformatic prediction analysis also determined that many cell cycle-associated factors were potentially transcribed by HOXB9. Collectively, the results of this study suggested that under the influence of the metastatic environment of the brain, lung tumor cells seemed to acquire phenotypic plasticity characterized by neural cell-like features, and this transition may be associated with the aberrant upregulation of HOXB9.